“Estrategia didáctica para el desarrollo del aprendizaje en los niños con necesidades educativas especiales asociadas al autismo en aulas de integralidad - Cordero Ruiz, Karina Alexandra (2023)
The work activities that are carried out in the Initial Level, with childrens, require special care, even more so if cases of special educational needs are added that require a more detailed vision and fundamental adaptations in which inclusion is highlighted; That is why it is proposed as a general objective: Design a didactic strategy for the development of learning in children with special educational needs associated with autism in comprehensive classrooms; To fulfill the purpose, the work methodology assumes a procedure based on a thorough understanding of the variables, the problem and the context of the Educational Institution in which it is developed; For this reason, the methodological criteria of the research assume a non-experimental qualitative approach, of a descriptive design. The development of a qualitative study allows an in-depth exploration of the narratives, opinions and perceptions of teachers regarding the inclusion processes, so that it is possible to generate a contribution to this topic, and the voices of the teachers are used as a source of evidence. teachers as central actors in the educational process. The results of the study show a marked difference between the diagnostic situation and the one obtained once the proposal has been implemented; This allows us to conclude that efficiently applied didactic strategies allow optimal results with students who have special educational needs associated with autism